Tau functions and their applications - Harnad, John P. 1946-; Balogh, Ferenc 1981- (Cambridge University Press, 2021)
Tau functions are a central tool in the modern theory of integrable systems. This volume provides a thorough introduction, starting from the basics and extending to recent research results. It covers a wide range of applications, including generating functions for solutions of integrable hierarchies, correlation functions in the spectral theory of random matrices and combinatorial generating functions for enumerative geometrical and topological invariants. A self-contained summary of more advanced topics needed to understand the material is provided, as are solutions and hints for the various exercises and problems that are included throughout the text to enrich the subject matter and engage the reader. Building on knowledge of standard topics in undergraduate mathematics and basic concepts and methods of classical and quantum mechanics, this monograph is ideal for graduate students and researchers who wish to become acquainted with the full range of applications of the theory of tau functions
Title from publisher's bibliographic system (viewed on 29 Jan 2021)
Keywords: Forms, Modular; Mathematical physics; Hamiltonian systems; Integral equations; Grassmann manifolds